Improvement of Background Solution for Optically Induced Dielectrophoresis-Based Cell Manipulation in a Microfluidic System - Chu, Po-Yu; Hsieh, Chia-Hsun; Chen, Chih-Yu; Wu, Min-Hsien (Frontiers in Bioengineering and Biotechnology, 2021)
Optically induced dielectrophoresis (ODEP) is effective for cell manipulation. However, its utilization has been limited by the requirement of solution with low conductivity. This issue has been ignored in ODEP-relevant studies. To address this issue, this study aims to investigate to what extent the cell viability and performance of ODEP-based cell manipulation are affected by low conductivity conditions. Additionally, this study aims to modify sucrose solutions to reduce the impacts caused by low-conductivity solutions. Results revealed the use of sucrose solution in ODEP operation could significantly reduce the viability of the manipulated cells by 9.1 and 38.5% after 2- and 4-h incubation, respectively. Prolonged operation time (e.g., 4 h) in sucrose solution could lead to significantly inferior performance of cell manipulation, including 47.2% reduction of ODEP manipulation velocity and 44.4% loss of the cells manipulatable by ODEP. The key finding of this study is that the use of bovine serum albumin (BSA)-supplemented sucrose solution (conductivity: 25–50 μS cm−1) might significantly increase the cell viability by 10.9–14.8% compared with that in sucrose solution after 4 h incubation. Moreover, the ODEP manipulation velocity of cells in the BSA-supplemented sucrose solution (conductivity: 25 μS cm−1) was comparable to that in sucrose solution during 4-h incubation. More importantly, compared with sucrose solution, the use of BSA-supplemented sucrose solution (conductivity: 25–50 μS cm−1) contributed high percentage (80.4–93.5%) of the cells manipulatable by ODEP during 4-h incubation. Overall, this study has provided some fundamental information relevant to the improvement of background solutions for ODEP-based cell manipulation.